Light transfer through semi-transparent glass panes supporting pendant droplets. (March 2021) - Simsek, Eylul; Zhu, Keyong; Kashanchi, Glareh N.; Williams, Megan J.; Galy, Tiphaine; Marszewski, Michal; Tolbert, Sarah H.; Pilon, Laurent
Highlights: Glass samples with droplet contact angle θc = 25-77 o, surface area coverage f A = 20-50%. For θ c < 42°, droplets did not affect the normal-hemispherical transmittance. For θ c > 42°, the transmittance decreased and reflectance increased with increasing θ c and f A . Observations were due to total internal reflection at the droplet/air interface. Measurements agreed well with predictions from the Monte Carlo Ray Tracing method. Abstract: This paper quantifies experimentally the effect of pendant droplets condensed on the back of semi-transparent glass panes on their normal-hemispherical transmittance and reflectance in the visible and near-infrared. To enable sample characterization and ensure repeatability, acrylic droplets were deposited on the back side of 3 mm-thick soda-lime silicate glass slabs with or without hydrophobic surface treatment including perfluorinated silane, perfluorinated silane-coated silica nanoparticle monolayer, or Teflon coatings. The droplet contact angle θc was varied between 26° and 76° and the projected surface area coverage reached up to 60%. For contact angle θc smaller than the critical angle θcr for total internal reflection at the droplet/air interface, the presence of droplets did not significantly affect the normal-hemispherical transmittance and reflectance. However, for droplet contact angle θcr ≤ θc < 90°, the normal-hemispherical transmittance decreased significantly with increasing droplet contact angle and/or surface area coverage while the normal-hemispherical reflectance increased. The measurements of the normal-hemispherical transmittance were in excellent agreement with numerical predictions obtained from Monte Carlo Ray Tracing method. These results further validate our previous numerical simulations and the different optical regimes identified. The results of this study can provide guidelines for the design and operation of energy efficient flat-plate solar collectors, outdoor photobioreactors, greenhouses, solar desalination systems, and other solar energy conversion systems.